High hyperdiploidy among adolescents and adults with acute lymphoblastic leukaemia (ALL): Cytogenetic features, clinical characteristics and outcome - Chilton, L; Buck, G; Harrison, C; Ketterling, R; Rowe, J; Tallman, MS; Goldstone, A; Fielding, A; Moorman, A (Nature Publishing Group, 2014)
High hyperdiploidy (HeH, 51-65 chromosomes) is an established genetic subtype of acute lymphoblastic leukaemia (ALL). The clinical and cytogenetic features as well as outcome of HeH among adolescents and adults have not been thoroughly investigated. Among 1232 B-cell precursor ALL patients (15-65 years) treated in the UKALLXII/ECOG2993 trial, 160 (13%) had a HeH karyotype, including 80 patients aged >24 years. The frequency of HeH was the same in Philadelphia chromosome (Ph)-positive and-negative cases, but Ph-positive patients were older. The cytogenetic profiles of Ph-positive and Ph-negative HeH cases were similar, although trisomy 2 was strongly associated with Ph-positive HeH. Overall, Ph-positive HeH patients did not have an inferior overall survival compared with Ph-negative patients (P=0.2: 50 vs 57% at 5 years). Trisomy of chromosome 4 was associated with a superior outcome in Ph-negative patients, whereas +5 and +20 were associated with an inferior outcome in Ph-positive and Ph-negative patients, respectively. All three markers retained significance in multivariate analysis adjusting for age and white cell count: hazard ratio for risk of death 0.47 (95% CI: 0.27-0.84) (P=0.01), 3.73 (1.51-9.21) (P=0.004) and 2.63 (1.25-5.54) (P=0.01), respectively. In conclusion, HeH is an important subtype of ALL at all ages and displays outcome heterogeneity according to chromosomal gain. © 2014 Macmillan Publishers Limited.